Comparison of microstructural, texture and mechanical properties of SiC and Zn particle reinforced FSW 6061-T6 aluminium alloy - Rahul Kesharwani; Kishor Kumar Jha; Murshid Imam; Chiranjit Sarkar; Imad Barsoum (Journal of Materials Research and Technology, 2023)
This work investigates the microstructure, mechanical characteristics, and texture evolution of friction stir welding (FSW) of AA6061-T6 metal matrix composites (MMCs) reinforced with silicon carbide (SiC) and zinc (Zn) particles. The SZ region of the SiC and Zn particle-reinforced aluminium matrix (Al-matrix) composites has ultra-fine grain refinements of 4.79 and 4.18 μm, respectively, compared to base metal (BM) particle sizes of 44.97 μm. Ultra-fine grain refinement in the SZ zone produces dynamic recrystallization with particulate-driven nucleation, Zenner Hollomon, and homogeneous SiC/Zn particle distribution in the Al-matrix. Recrystallization texture components P {011} <112>, cube {001} <101>, rotating cube (H) {001} <110>, and F {111} <112>, along with primary shear texture components (B/B¯, and C), suggested DRX at the joint interface in the SiC-reinforced Al-matrix composite. However, the Zn-reinforced Al-matrix composite has a high plain strain, recrystallization, and deformation texture components of copper {112} <111>, Brass {011} <211>, cube {001} <101>, Goss {110}, and P 011 <112>, and major shear texture components (B/B¯ and C). SiC and Zn-reinforced Al-matrix composites have 110 ± 4 and 120 ± 5 HV0.2 average microhardness, respectively. Also, SiC and Zn-reinforced Al-matrix composites have 224 and 236 MPa tensile strengths, respectively.